Pendampingan Wawasan Kesejarahan Indonesia dan Literasi terhadap Anak-anak - Pratama, Cahya Adhitya; Valenda, Rani; Purnomo, Arif; Wulandari, Vika Aulia; Sri, Nida Widia; Gunawan, Rudy; Susanti, Eka Desy (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2022)
KKN-Dik activities are a form of activity that supports students' ability to socialize. Because students have the task of education, research and service. This KKN activity is one of the student's tasks to serve the community. In the community, it becomes a laboratory for students, because all the learning processes obtained on campus can be implemented in the community so that they can help and develop in the village. Historical insight is one of the important things to know the history of the nation and the country. In addition, reading literacy is also a major component to form a superior young generation. Therefore, the purpose of this community service is to provide assistance with insight into Indonesian history and reading literacy in order to form a good character and identity as well as an embedded sense of nationalism. The method used is the guidance and delivery of material carried out by students to the children of Mekarsari Village. As a result of this community service, the children of Mekarsari Village have understood and understood the events of Indonesian history and began to be interested in continuing to read.